2022
DOI: 10.2334/josnusd.22-0085
|View full text |Cite
|
Sign up to set email alerts
|

Surface degradation and biofilm formation on hybrid and nanohybrid composites after immersion in different liquids

Abstract: Purpose: This study evaluated the association of surface degradation and formation of Streptococcus mutans (S. mutans) biofilm in resin-based composites (RBCs) after storage in different acidic liquids. Methods: To evaluate microhardness and surface micromorphology, hybrid and nanohybrid RBC discs were stored in artificial gastric acid, cola drink, orange juice, artificial saliva, and distilled water for three intervals of 15 min per day for 7, 15, and 30 days. After 30 days of storage, surface roughness was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…Despite the lack of previous studies that agree on the multiple interactions of types of manufacturing, mouthrinses, and measuring time, our results were consistent with the findings reported in other studies. Previous research found that NCR showed less VHN involvement than hybrids when exposed to acidic liquids (pH ≤ 3.2) after 7 days [24] and 15 days [23]. Another study found less VHN involvement in Z350 XT resins, especially when exposed to CHX at 0.12 (pH = 6.07) compared to other classifications of resin fillers and mouthrinses with a lower pH (<4.1) after 7 days [25].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Despite the lack of previous studies that agree on the multiple interactions of types of manufacturing, mouthrinses, and measuring time, our results were consistent with the findings reported in other studies. Previous research found that NCR showed less VHN involvement than hybrids when exposed to acidic liquids (pH ≤ 3.2) after 7 days [24] and 15 days [23]. Another study found less VHN involvement in Z350 XT resins, especially when exposed to CHX at 0.12 (pH = 6.07) compared to other classifications of resin fillers and mouthrinses with a lower pH (<4.1) after 7 days [25].…”
Section: Discussionmentioning
confidence: 92%
“…Determination of surface VHN is a conventional noninvasive technique frequently used to evaluate the physical properties of biomaterials such as resins [22,23]. Greater resistance of the composite to indentation represents opposition to the influence of other structures providing greater durability over time and a lower risk of replacement due to failure [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the main scientific evidence that was obtained through the analysis of the articles selected in this study, photoactivated composite resins were introduced in dentistry in the past decades, and are the first choice materials for direct restorations due to the evolution of their properties, such as color, brightness, surface smoothness, translucency and opacity that enable the aesthetic reconstruction of dental structures Initially, the restorative material was photoactivated by ultraviolet light, however, because of the harmful effects of radiation, this type of photoactivation fell into disuse [15].…”
Section: Major Findings -Composite Resin and Biofilmmentioning
confidence: 99%
“…Pocos estudios han evaluado la rugosidad (Ra) de las resinas después de la inmersión exclusiva en bebidas carbonatadas. En experimentos in vitro se halló que la Ra aumentó en superficies de resinas nanohíbridas, híbridas, microhíbridas y de nanorrelleno, frente a la exposición de bebidas ácidas como gaseosa, té, café o naranja ( 5,(21)(22)(23)(24) ).…”
Section: Introductionunclassified